Pelayanan dan Fasilitas Kesehatan, Biaya Persalinan, dan Kebijakan di Tempat Bersalin Mempengaruhi Ibu Dalam Memilih Tempat Bersalin di Kelurahan Kemiri Muka, Kecamatan Beji, Depok - Nourmayansa Vidya; Apriyanti, Efa; Agustina, Ayunda Nia; Fathmanda, Maharaufa (Journal of Health Education and Literacy, 2020)
One indicator of a country's health status is the maternal and infant mortality rate. 52.4% of mothers in Indonesia have access to maternal services. Maternal Mortality Rate (MMR) in Indonesia in 2008 according to the Demographic Health Survey of Indonesia is 307 per 100,000 live births, its far from the supposed target of 110 per 100,000 live births. The general objective of this study was to determine the factors associated with mother's decision when choosing a birth place, including the choice of giving birth. The factors that affect mother's decision when choosing a birth place are characteristic of the respondents and distance delivery and home place. Research sample is mothers residing in RW 03 Kelurahan Kemiri Muka - Depok totaling 125 people. This study uses a questionnaire and return rate = 100%. This study uses cross sectional data analysis using univariate and bivariate frequency distribution using the chisquare test. The results showed that there was a significant relationship between respondent’s education (p-value = 0.009; = 0.05), the husband's income & (pvalue = 0.046; = 0.05), and health facilities (p -value = 0.033; = 0.05) with a choice of place of birth.